Stabilization of p22phox by hypoxia promotes pulmonary hypertension - Zhang, Zuwen; Weitnauer, Michael (Antioxidants & redox signaling, 2019)
Aims: Hypoxia and reactive oxygen species (ROS) have been shown to play a role in the pathogenesis of pulmonary hypertension (PH), a potentially fatal disorder characterized by pulmonary vascular remodeling, elevated pulmonary arterial pressure, and right ventricular hypertrophy. However, how they are linked in the context of PH is not completely understood. We, therefore, investigated the role of the NADPH oxidase subunit p22phox in the response to hypoxia both in vitro and in vivo.Results: We found that hypoxia decreased ubiquitinylation and proteasomal degradation of p22phox dependent on prolyl hydroxylases (PHDs) and the E3 ubiquitin ligase protein von Hippel Lindau (pVHL), which resulted in p22phox stabilization and accumulation. p22phox promoted vascular proliferation, migration, and angiogenesis under normoxia and hypoxia. Increased levels of p22phox were also detected in lungs and hearts from mice with hypoxia-induced PH. Mice harboring a point mutation (Y121H) in the p22phox gene, which resulted in decreased p22phox stability and subsequent loss of this protein, were protected against hypoxia-induced PH. Mechanistically, p22phox contributed to ROS generation under normoxia, hypoxia, and hypoxia/reoxygenation. p22phox increased the levels and activity of HIF1α, the major cellular regulator of hypoxia adaptation, under normoxia and hypoxia, possibly by decreasing the levels of the PHD cofactors ascorbate and iron(II), and it contributed to the downregulation of the tumor suppressor miR-140 by hypoxia.Innovation: These data identify p22phox as an important regulator of the hypoxia response both in vitro and in vivo.Conclusion: p22phox-dependent NADPH oxidases contribute to the pathophysiology of PH induced by hypoxia.